Complexity and interpretability in global change ecology - Montoya, D.; Buron-Ugarte, A.; Chretien, L. T. S.; Christensen Garcia, C.; Granjel, R. R.; Holmes, M.; Huang, M.; Iglesias-Anciones, L.; Larretxi-Gallastegi, I.; Porras-Gomez, J. (2025)
Ecological systems are inherently complex. Global change- including the impacts of climate change- affects them in varied ways, and they respond in diverse forms. Any attempt to stem the current biodiversity crisis should account for this complexity while simultaneously reaching a general understanding of how ecological systems respond to global change. Here, we briefly introduce three axes of complexity in global change ecology and discuss how our approaches to understand it can be maximised.